Methicillin-resistant staphylococci. - Chambers, H F (1988)
Strains of staphylococci resistant to methicillin were identified immediately after introduction of this drug. Methicillin-resistant strains have unusual properties, the most notable of which is extreme variability in expression of the resistance trait. The conditions associated with this heterogeneous expression of resistance are described. Methicillin resistance is associated with production of a unique penicillin-binding protein (PBP), 2a, which is bound and inactivated only at high concentrations of beta-lactam antibiotics. PBP2a appears to be encoded by the mec determinant, which also is unique to methicillin-resistant strains. The relationships between PBP2a and expression of resistance and implications for the mechanism of resistance are discussed. The heterogeneous expression of methicillin resistance by staphylococci poses problems in the detection of resistant strains. Experience with several susceptibility test methods is reviewed and guidelines for performance of these tests are given. Treatment of infections caused by methicillin-resistant staphylococci is discussed. Vancomycin is the treatment of choice. Alternatives have been few because methicillin-resistant strains often are resistant to multiple antibiotics in addition to beta-lactam antibiotics. New agents which are active against methicillin-resistant staphylococci are becoming available, and their potential role in treatment is discussed.